Implementation of trauma-informed care and trauma-responsive services in clinical settings: a latent class regression analysis - Anderson, Katherine M.; Piper, Kaitlin N.; Kalokhe, Ameeta S.; Sales, Jessica M. (Frontiers in Psychiatry, 2023)
Introduction: Engagement and retention in health care is vital to sustained health among people living with HIV (PLWH), yet clinical environments can deter health-seeking behavior, particularly for survivors of interpersonal violence. PLWH face disproportionate rates of interpersonal violence; clinical interactions can provoke a re-experiencing of the sequalae of trauma from violence, called retraumatization. Trauma-informed care (TIC) is a strengths-based approach to case that minimizes potential triggers of re-traumatization and promotes patient empowerment, increasing acceptability of care. Yet, Ryan White HIV/AIDS clinics, at which over 50% of PLWH received care, have struggled to implementation TIC. In this analysis, we sought to (1) identify unique sub-groups of HIV clinics based on clinical attributes (i.e., resources, leadership, culture, climate, access to knowledge about trauma-informed care) and (2) assess relationships between sub-group membership and degree of implementation of TIC and trauma-responsive services offered.Methods: 317 participants from 47 Ryan White Federally-funded HIV/AIDS clinics completed a quantitative survey between December 2019 and April 2020. Questions included assessment of inner setting constructs from the Consolidated Framework for Implementation Research (CFIR), perceived level of TIC implementation, and trauma-responsive services offered by each respondent's clinic. We employed latent class analysis to identify four sub-groups of clinics with unique inner setting profiles: Inner Setting Weak (n=124, 39.1%), Siloed and Resource Scarce (n=80, 25.2%), Low Communication (n=49, 15.5%), and Inner Setting Robust (n=64, 20.2%). We used multilevel regressions to predict degree of TIC implementation and provision of trauma-responsive services.Results: Results demonstrate that clinics can be distinctly classified by inner setting characteristics. Further, inner setting robustness is associated with a higher degree of TIC implementation, wherein classes with resources (Robust Inner Setting, Low Communication) are associated with significantly higher odds reporting early stages of implementation or active implementation compared to Weak 2 This is a provisional file, not the final typeset article class membership. Resourced class membership is also associated with availability of twice as many trauma-responsive services compared to Weak class membership.Discussion: Assessment of CFIR inner setting constructs may reveal modifiable implementation setting attributes key to implementing TIC and trauma-responsive services in clinical settings.